Study of Hydrate Formation and Inhibition for LPG (Journal of Chemical Engineering, 2014)
Liquefied petroleum gas (LPG) has already been proved as an efficient fuel and feedstock for many chemical and petrochemical industries. Hydrate formation can create serious problems in the production, transmission, storage, and end-use of LPG. Hence an adequate knowledge on hydrate formation (i.e., the effects of moisture content and pressure on the hydrate formation temperature) is crucial to maintain the process conditions out of the hydrate formation region. However the study particularly on such aspects is scarcely available in literature. Therefore the effects of moisture content and pressure on the LPG hydrate formation temperature are studied extensively. A correlation is also developed to predict hydrate formation temperature for various LPG compositions. Hydrate inhibition performances of various inhibitors are also evaluated. Aspen-HYSYS process simulator is used to perform the study. The present study provides useful information to reduce the hydrate formation of LPG. DOI: http://dx.doi.org/10.3329/jce.v27i2.17804 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 60-64